2003
DOI: 10.1210/en.2001-210109
|View full text |Cite
|
Sign up to set email alerts
|

p53 Is Required for 1,25-Dihydroxyvitamin D3-Induced G0 Arrest But Is Not Required for G1 Accumulation or Apoptosis of LNCaP Prostate Cancer Cells

Abstract: 1,25-Dihydroxyvitamin D(3) [1,25-(OH)(2)D(3)] is an effective agent for inhibiting the growth of prostate cancer cells including LNCaP and PC-3 cell lines. However, the extent of growth inhibition in these cell lines differs because LNCaP cells are much more responsive than PC-3 cells. Previous studies in LNCaP cells have shown that 1,25-(OH)(2)D(3) treatment results in G(0)/G(1) cell cycle accumulation, loss of Ki67 expression, and induction of apoptosis. One difference between the two cell lines is that PC-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 54 publications
3
30
0
1
Order By: Relevance
“…In previous studies, we have established that both of these readouts are proportional to cell number and thus these assays, while different, are readily comparable (Peehl et al, 1994;Rashid et al, 2001a). Reflective of this, the ED 50 values of normal cultures in the two assays were comparable, which we attribute to 1a,25(OH) 2 D 3 having a pleiotropic set of actions regulating both cell cycle progression, proliferation and invasion (Blutt et al, 1997(Blutt et al, , 2000Schwartz et al, 1997;Polek et al, 2003). Elevated SMRT in PC-3 and DU-145 correlated with their insensitivity to 1a,25(OH) 2 D 3 (ED 50 4100 nM).…”
Section: Smrt Mrna Levels Are Elevated In Prostate Cancer Cell Lines mentioning
confidence: 57%
“…In previous studies, we have established that both of these readouts are proportional to cell number and thus these assays, while different, are readily comparable (Peehl et al, 1994;Rashid et al, 2001a). Reflective of this, the ED 50 values of normal cultures in the two assays were comparable, which we attribute to 1a,25(OH) 2 D 3 having a pleiotropic set of actions regulating both cell cycle progression, proliferation and invasion (Blutt et al, 1997(Blutt et al, , 2000Schwartz et al, 1997;Polek et al, 2003). Elevated SMRT in PC-3 and DU-145 correlated with their insensitivity to 1a,25(OH) 2 D 3 (ED 50 4100 nM).…”
Section: Smrt Mrna Levels Are Elevated In Prostate Cancer Cell Lines mentioning
confidence: 57%
“…Since GSTp transfection only partly inhibited As 2 O 3 -induced apoptosis in LNCaP/GSTp cells (Figure 7), other factors in addition to GSTp may also account for the differential sensitivity of LNCaP cells comparing to that It is well known that p53 protein mediates apoptosis induction due to many chemotherapeutic agents (Blagosklonny, 2002). LNCaP cells contain wild-type p53 and both DU-145 and PC-3 contain mutant p53 (Polek et al, 2003). It was found that p53 protein was induced by As 2 O 3 in LNCaP cells, which correlated with apoptosis induction (Figures 7 and 10).…”
Section: Discussionmentioning
confidence: 99%
“…Those investigators also did not find a significant apoptotic response to VD therapy in TPC1. A possible explanation for the lack of cell cycle arrest seen in C643 is that this cell line harbors a mutant p53, where a WT p53 gene has been reported as necessary for cell cycle arrest in response to calcitriol therapy in a prostate cancer cell model (35,36).…”
Section: Figmentioning
confidence: 99%